From concept to crystals via prediction: multicomponent organic cage pots by social selfsorting - Jelfs,K; Greenaway,RL; Santolini,V; Pulido,A; Little,MA; Alston,BM; Briggs,ME; Day,GM; Cooper,AI (Angewandte Chemie International Edition, 2019)
We describe the a priori computational prediction and realization of multicomponent cage pots, starting with molecular predictions based on candidate precursors through to crystal structure prediction and synthesis using robotic screening. The molecules were formed by the social selfsorting of a tritopic aldehyde with both a tritopic amine and ditopic amine, without using orthogonal reactivity or precursors of the same topicity. Crystal structure prediction suggested a rich polymorphic landscape, where there was an overall preference for chiral recognition to form heterochiral rather than homochiral packings, with heterochiral pairs being more likely to pack windowtowindow to form twocomponent capsules. These crystal packing preferences were then observed in experimental crystal structures.